Clinical Profile of Brain Tumour in Children (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: This study was designed to evaluate the clinical profile and location of brain tumours in children so that brain tumour cases could be diagnosed and managed earlier.Materials and Methods: This cross sectional study was carried out from April 2011 to April 2012. A total 50 clinically suspected cases of brain tumour and supported by MRI were enrolled in this study.Results: Brain tumour of children was predominant in male where male to female ratio was almost 1.9:1. Supratentorial and Infratentorial brain tumour were found in 36% and 64% cases respectively in children. According to MRI findings in the supratentorial location, craniopharyngioma were commonest (50%) followed by cerebral astrocytoma (22.2%). In the infratentorial region, medulloblastoma was observed in (40.6%), followed by cerebellar astrocytoma (31.3%). Vertigo, weakness of limbs were found in 46.9% and 87.5% cases respectively in infratentorial group which were significantly (p